2023
DOI: 10.14218/erhm.2022.00118
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profile and Antioxidant Activities of Three Date Seeds Varieties (Phoenix Dactylifera L.) of Pakistan

Abstract: Background and objectives: This work aimed to evaluate the phenolic profile and antioxidant capacity of water extracts of three different date seed varieties i.e., Aseel, Karbalaen and Khupro. Date (Phoenix dactylifera L.) seeds are available in bulk quantities after manufacturing of pitted dates or syrup and are considered as waste stream.Methods: Total phenolic content in date seeds was determined with Folin-Ciocalteu's phenol reagent. The phenolic compounds profile was determined by high performance liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In addition, this activity could not be attributed to any of the detected phenolic compounds, which suggests the role of a certain polyphenol that was not detected on HPLC analysis due to limited standards used. P-coumaric acid, sinapic acid, and chlorogenic acid were found to be dominant in date seeds but were not included as standards in our HPLC analysis for comparison between the examined date seed varieties [ 12 , 37 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this activity could not be attributed to any of the detected phenolic compounds, which suggests the role of a certain polyphenol that was not detected on HPLC analysis due to limited standards used. P-coumaric acid, sinapic acid, and chlorogenic acid were found to be dominant in date seeds but were not included as standards in our HPLC analysis for comparison between the examined date seed varieties [ 12 , 37 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, lauric acid, which is classified as a saturated fatty acid, was found to be preferable to trans-fatty acids in terms of disruption of lipid profile [ 56 ]. It also appeared to possess some antibacterial properties, as it inhibited the growth of pathogenic bacteria (especially S. aureus ) and reduced their ability to produce toxins [ 37 , 49 , 50 ]. Interestingly, lauric and mystric acids, which are both present in date seed oils, revealed preventive effects on the development of prostatic hyperplasia [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fruit of date palm is a rich source of nutrients and high content of bioactive substances like phenolic compounds. It also possesses variety of therapeutic potential such as antioxidant, antimicrobial, anti-inflammatory and others (10). Date palm is supposed as a complete diet and medicinal plant as phytochemical studies have explained that the date palm contains anthocyanins, phenolics, sterols, carotenoids, and flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the types of solvents and their polarity have an impact on the solubility of polyphenols (14,21), and the date-seeds contain a variety of polyphenols, each of which may have a distinct polarity. In comparison to a solvent that is just aqueous, acetone in aqueous solution dissolves hydrophilic and high molecular weight molecules (10). One of study reported that phenolics and flavonoids had comparable extraction patterns, with 50% aqueous acetone producing the best results comparative to pure acetone (7).…”
Section: Discussionmentioning
confidence: 99%